2003
DOI: 10.1046/j.1540-8167.2003.03206.x
|View full text |Cite
|
Sign up to set email alerts
|

Fasciculoventricular Pathways:

Abstract: Electrophysiologists should be able to make the differential diagnosis between a fasciculoventricular bypass tract and an anteroseptal accessory pathway to preclude potential harm to the AV conduction system if a fasciculoventricular pathway is targeted for catheter ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…5 While a higher association of FVP has been recently reported in patients with hypertrophic cardiomyopathy and PRKAG2 variants, there is scarce literature on their presence in Danon disease. [6][7][8] The purpose of this study is twofold. First, to elucidate the electrical properties and arrhythmia outcomes of patients with Danon disease at our institute, and second, to describe the presence of FV pathways in this population.…”
Section: Introductionmentioning
confidence: 99%
“…5 While a higher association of FVP has been recently reported in patients with hypertrophic cardiomyopathy and PRKAG2 variants, there is scarce literature on their presence in Danon disease. [6][7][8] The purpose of this study is twofold. First, to elucidate the electrical properties and arrhythmia outcomes of patients with Danon disease at our institute, and second, to describe the presence of FV pathways in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in symptomatic patients, the etiology may be related to other arrhythmogenic substrates and not the FV pathway itself. The FV pathway can have overlapping ECG features with manifest anteroseptal and midseptal accessory pathways and therefore should be correctly identified to avoid unnecessary catheter ablation and inadvertent AV nodal damage 4 . Formal electrophysiological testing in our 2 cases revealed that the observed preexcitation patterns were consistent with FV connections rather than WPW syndrome.…”
Section: Discussionmentioning
confidence: 71%
“…Fasciculoventricular (FV) pathways that manifest after CHD surgery have not been described previously. Although FV pathways do not participate in arrhythmias, their effects manifest as de novo preexcitation on surface electrocardiograms (ECGs) 4 . We present 2 cases of apparent acquired FV pathways and describe the potential mechanism of development following CHD surgery.…”
Section: Introductionmentioning
confidence: 99%
“…FVP is very rare, occurring in 1.2% to 5.1% of patients with symptomatic preexcitation 8, 9, 10, 11. No data have been published or presented regarding the prevalence in patients without symptoms.…”
Section: Discussionmentioning
confidence: 99%